Defining the hypoxic target volume based on positron emission tomography for image guided radiotherapy – the influence of the choice of the reference region and conversion function. (4th May 2017) - Lindblom, Emely; Dasu, Alexandru; Uhrdin, Johan; Even, Aniek; van Elmpt, Wouter; Lambin, Philippe; Wersäll, Peter; Toma-Dasu, Iuliana
Abstract: Background: Hypoxia imaged by positron emission tomography (PET) is a potential target for optimization in radiotherapy. However, the implementation of this approach with respect to the conversion of intensities in the images into oxygenation and radiosensitivity maps is not straightforward. This study investigated the feasibility of applying two conversion approaches previously derived for 18 F-labeled fluoromisonidazole ( 18 F-FMISO)-PET images for the hypoxia tracer 18 F-flortanidazole ( 18 F-HX4). Material and methods: Ten non-small-cell lung cancer patients imaged with 18 F-HX4 before the start of radiotherapy were considered in this study. PET image uptake was normalized to a well-oxygenated reference region and subsequently linear and non-linear conversions were used to determine tissue oxygenations maps. These were subsequently used to delineate hypoxic volumes based partial oxygen pressure (pO2 ) thresholds. The results were compared to hypoxic volumes segmented using a tissue-to-background ratio of 1.4 for 18 F-HX4 uptake. Results: While the linear conversion function was not found to result in realistic oxygenation maps, the non-linear function resulted in reasonably sized sub-volumes in good agreement with uptake-based segmented volumes for a limited range of pO2 thresholds. However, the pO2 values corresponding to this range were significantly higher than what is normally considered as hypoxia. The similarity in size, shape, and relative location between uptake-based sub-volumes and volumes based on the conversion to pO2 suggests that the relationship between uptake and pO2 is similar for 18 F-FMISO and 18 F-HX4, but that the model parameters need to be adjusted for the latter. Conclusions: A non-linear conversion function between uptake and oxygen partial pressure for 18 F-FMISO-PET could be applied to 18 F-HX4 images to delineate hypoxic sub-volumes of similar size, shape, and relative location as based directly on the uptake. In order to apply the model for e.g., dose-painting, new parameters need to be derived for the accurate calculation of dose-modifying factors for this tracer.